Brain glycogen—new perspectives on its metabolic function and regulation at the subcellular level - Obel, Linea F.; Müller, Margit S.; Walls, Anne B.; Sickmann, Helle M.; Bak, Lasse K.; Waagepetersen, Helle S.; Schousboe, Arne (Frontiers in Neuroenergetics, 2012)
Glycogen is a complex glucose polymer found in a variety of tissues, including brain, where it is localized primarily in astrocytes. The small quantity found in brain compared to e.g. liver has led to the understanding that brain glycogen is merely used during hypoglycemia or ischemia. In this review evidence is brought forward highlighting what has been an emerging understanding in brain energy metabolism: that glycogen is more than just a convenient way to store energy for use in emergencies – it is a highly dynamic molecule with versatile implications in brain function, i.e. synaptic activity and memory formation. In line with the great spatiotemporal complexity of the brain and thereof derived focus on the basis for ensuring the availability of the right amount of energy at the right time and place, we here encourage a closer look into the molecular and subcellular mechanisms underlying glycogen metabolism. Based on i) the compartmentation of the interconnected second messenger pathways controlling glycogen metabolism (calcium and cAMP), ii) alterations in the subcellular location of glycogen-associated enzymes and proteins induced by the metabolic status and iii) a sequential component in the intermolecular mechanisms of glycogen metabolism, we suggest that glycogen metabolism in astrocytes is compartmentalized at the subcellular level. As a consequence, the meaning and importance of conventional terms used to describe glycogen metabolism (e.g. turnover) is challenged. Overall, this review represents an overview of contemporary knowledge about brain glycogen and its metabolism and function. However, it also has a sharp focus on what we do not know, which is perhaps even more important for the future quest of uncovering the roles of glycogen in brain physiology and pathology.